Anti-inflammatory and immunomodulatory effects of rosuvastatin in patients with low-to-moderate cardiovascular risk - VAVLUKIS ANA; VAVLUKIS MARIJA; DIMOVSKI ALEKSANDAR; PETRUSHEVSKA GORDANA; EFTIMOV ALEKSANDAR; DOMAZETOVSKA SASHKA; MLADENOVSKA KRISTINA (Acta Pharmaceutica)
Statins have shown anti-inflammatory pleiotropic effects in subjects with/at risk of cardiovascular disease. The aim of this study was to evaluate the inflammatory/immunomodulatory properties of rosuvastatin in subjects at low-to-moderate cardiovascular risk. Data was collected from patients’ records, physical examination and blood sampling. Subjects were assigned to rosuvastatin 20 mg per day. Rosuvastatin significantly decreased C-reactive protein (p = 0.045), and increased vascular endothelial growth factor (p = 0.004) and epidermal growth factor (p = 0.009). A multivariate analysis identified total cholesterol (p = 0.027) and vascular endothelial growth factor (p = 0.011) to be independently associated with rosuvastatin treatment. Given beneficial/harmful role of growth factors, vascular endothelial growth factor (VEGF) and epidermal growth factor (EGF), in cardiovascular disease, one would suggest the need for routine monitoring of growth factor levels, especially in patients on long-term statin therapy.